Complete microbiological analysis of citrus fruits and the effect of heat on microbial load & antimicrobial activity (Stamford Journal of Microbiology, 2017)
Citrus fruits are very popular both for raw consumption as well as juices, jam and jelly. Besides the nutritional properties, citrus fruits exhibit some antimicrobial properties by containing polymethoxylated flavones, flavonoids, steroids, saponins, alkaloids, reducing sugars, terpenoids etc. But sometimes such fruits can be contaminated with bacteria which find their ways in the consumers causing different disease conditions. The current study revealed the microbial load of Lemon, Lotkone, Orange, Malta and Amoloki and the study showed complete absence of Klebsiella spp. and Escherichia coli. The highest total viable bacterial and fungal count was 4.2×104 cfu/g and 2.0×105 cfu/g respectively. Pseudomonas spp. was the highest predominating bacteria with lower degree of contamination by Listeria spp. and Staphylococcus spp. Applying heat at 60oC for 30 minutes, 1 hour and 2 hours proved the reduction of bacteria over time. Antibacterial activity after heat treatment for all cases (after 30 minutes, 1 hour and 2 hours). Antibacterial activity was lowest after 2 hours of heat treatment for amoloki and there was no such activity at all for Amra after 2 hours. Other citrus fruits surprisingly showed no antibacterial activity after heat treatment.Stamford Journal of Microbiology, Vol.7(1) 2017: 28-32